The Case-Based Collaborative Learning Peer Observation Worksheet and Compendium: An Evaluation Tool for Flipped Classroom Facilitators - Susan Frankl; Lori Newman; Susan Burgin; Ayse Atasoylu; Laurie Fishman; Holly Gooding; Daniel Kamin; Alberto Puig; Ann-Marie Thomas; David Cohen; Richard Schwartzstein (Association of American Medical Colleges, 2017)
Introduction In a flipped classroom, students learn basic concepts before class, allowing them time during class to apply newly gained knowledge to problem sets and cases. Harvard Medical School (HMS) has introduced a form of flipped classroom, called case-based collaborative learning (CBCL), during preclinical curricula. Finding few published resources, the HMS Academy's Peer Observation of Teaching Interest Group developed a guide for observations and feedback to CBCL facilitators. Methods After conducting an extensive literature search, speaking to flipped classroom methodology experts, and observing 14 facilitators using CBCL methods, the interest group identified specific teaching behaviors that optimize student interaction and knowledge application. The group next engaged in several rounds of the modified Delphi method to develop the CBCL peer observation worksheet and compendium and then tested these materials' effectiveness in capturing CBCL teaching behaviors and providing feedback to CBCL faculty facilitators. Results Seventy-three percent of faculty rated the worksheet and compendium as extremely helpful or helpful in identifying new teaching techniques. Moreover, 90% found the CBCL peer observation and debriefing to be extremely helpful or helpful, and 90% were extremely likely or likely to incorporate peer suggestions in future teaching sessions. Discussion Medical schools have begun to embrace flipped classroom methods to eliminate passive, lecture-style instruction during the preclinical years of the MD curriculum. This tool identifies specific in-classroom approaches that engage students in active learning, guides peer observers in offering targeted feedback to faculty on teaching strategies, and presents consensus-based resources for use during CBCL faculty development and training.